Gene transfer and gene therapy - Williams, David A. (Henry Stewart Talks, 2015)
Definition of gene therapy, Requirements for successful gene therapy, Vector systems with application for blood diseases, Experience in clinical trials, Insertional mutagenesis, Prospects and new approaches